2021
DOI: 10.1016/j.ijpam.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 25-hydroxy vitamin D level with neonatal hyperbilirubinemia in term healthy newborn

Abstract: Background: Neonatal hyperbilirubinemia is one of the common entities that lead to frequent hospital admission of newborn. There are many risk factors that, when present, can lead to increased chances of neonatal hyperbilirubinemia. It is essential to identify these risk factors that are involved in the increased incidence of neonatal hyperbilirubinemia because its incidence can be decreased by modifying them. Objective: To compare and determine any cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…At present, the relationship between vitamin D levels and neonatal hyperbilirubinemia has attracted widespread attention. There have been many epidemiological studies on the relationship between vitamin D levels and neonatal hyperbilirubinemia, and some reports have shown that newborns with hyperbilirubinemia are negatively correlated with their serum vitamin D levels [13][14][15][16][17]. However, there are also studies suggesting that there is no significant correlation between serum vitamin D levels and neonatal hyperbilirubinemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the relationship between vitamin D levels and neonatal hyperbilirubinemia has attracted widespread attention. There have been many epidemiological studies on the relationship between vitamin D levels and neonatal hyperbilirubinemia, and some reports have shown that newborns with hyperbilirubinemia are negatively correlated with their serum vitamin D levels [13][14][15][16][17]. However, there are also studies suggesting that there is no significant correlation between serum vitamin D levels and neonatal hyperbilirubinemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Low maternal vitamin D levels have been associated with these findings [36]. The mechanism behind this association is unknown, but it is speculated that as both bilirubin and vitamin D are metabolized in the liver, there may be an interaction exacerbating hyperbilirubinemia [35]. We do not think this a likely outcome in our study, as although nutrient supplements contain vitamin D, mothers were on routine vitamin D supplements during pregnancy.…”
Section: Discussionmentioning
confidence: 64%
“…TSBR significantly declined in vitamin D treated infants on phototherapy compared to those on phototherapy alone [34]. Neonates with out of physiological range TSBR have been shown to be vitamin D deficient compared to controls [35]. Low maternal vitamin D levels have been associated with these findings [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is basic to distinguish the danger factors that are associated with the expanded rate of neonatal jaundice since its occurrence can be diminished by changing them [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient D is one of the fat-dissolvable nutrients in fact thought about a hormone. Numerous elements of nutrient D have been decoded in clinical exploration [2].…”
Section: Introductionmentioning
confidence: 99%